EFFECT OF AGARICUS BISPORUS AND ORIGANUM MAJORANA L EXTRACT ON THE SHELF-LIFE AND NUTRITIONAL PROPERTIES OF PORK LIVER PÂTÉ - ȚIBULCĂ, Dorin; FOGARASI, Melinda; SOCACI, Sonia Ancuţa; FOGARASI, Szabolcs; POP, Carmen; SĂLĂGEAN, Dan; TOFANĂ, Maria; MICHIU, Delia (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The current study aimed to examine the effects of Agaricus bisporus and O. marjorana extract and their beneficial impact on the shelf-life and nutritional changes occurring in pork liver pâté during storage time. Based on the obtained result, regarding the characterization of O. marjorana essential oil (OMEO) and mushroom powder, three types of pork liver pâté were formulated with different proportion of OMEO and mushroom powder and they were sensory evaluated using the 9-point hedonic test. In order to determine the stability during storage time, the selected sample and the control sample were sampled initially, after 30, 60, 90 and 120 days of storage than subjected to physicochemical (protein, fat, moisture, ash, total carbohydrates, and energy) evaluation.